2022
DOI: 10.1002/cnm.3586
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical modeling of novel high expansion auxetic skin grafts

Abstract: Over 20 million burn injuries are reported every year, with severe cases requiring skin grafting. Traditionally, split thickness skin grafts are prepared by excising a small portion of healthy skin and its incision patterning using a suitable meshing device, which allows the graft to be expanded beyond its capacity. To date, the maximum expansion achieved through skin grafting has been reported to be less than three times, which is not sufficient for covering large burn sites with limited donor site skin. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Beyond this, hyperelastic modelling was invoked to simulate polymeric nonlinear stiffening effects. All the outsoles were meshed with 10-node SOLID 187 tetrahedral elements to facilitate ease in mesh convergence and enhance the models' accuracy [41][42][43]. The outsoles were computationally warped at an angle of 17°and a force of 275 N was evenly applied over the upper surface of the outsole model.…”
Section: Cfd Modelling For the Prediction Of Fluid Pressuresmentioning
confidence: 99%
“…Beyond this, hyperelastic modelling was invoked to simulate polymeric nonlinear stiffening effects. All the outsoles were meshed with 10-node SOLID 187 tetrahedral elements to facilitate ease in mesh convergence and enhance the models' accuracy [41][42][43]. The outsoles were computationally warped at an angle of 17°and a force of 275 N was evenly applied over the upper surface of the outsole model.…”
Section: Cfd Modelling For the Prediction Of Fluid Pressuresmentioning
confidence: 99%
“…It is commonly used to treat burns, wounds, and other injuries that have damaged the skin. While skin grafting has been successful in many cases, this procedure faces some global issues (i.e., limited donor skin, cost, lack of suitable donors, donor site morbidity) [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that the randomly oriented cut auxetic structure exhibited a maximum negative Poisson's ratio value of −0.8 under maximum deformation. In literature, several studies were performed to understand the effect of structural parameters such as unit cell length, spacing and orientation in Poisson's ratio [22,[47][48][49]. Based upon the previous studies, on increasing the axial length of the slits, the effective Poisson's ratio decreased [23,50,51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In universal testing machine (UTM), one end is fixed, and the other end is moving with specific strain rates, while the force-displacement data is collected. The most common way to characterize isotropic materials is through uniaxial tests [19][20][21][22]. However, soft tissues are viscoelastic, and exhibit anisotropic material properties [2,23,24].…”
Section: Introductionmentioning
confidence: 99%